Effect of Grape Maturity and Juice Treatments on Terpene Concentrations and Wine Quality of Vitis vinifera L. cv. Weisser Riesling and Bukettraube - Marais, J.; van Wyk, C.J. (South African Journal of Enology and Viticulture, 2017)
The effect of grape maturity aud different juice treatments, namely free-run, skin-contact, pressing and heat treatment on individual terpene concentrations in Weisser Riesling and Bukettraube juices and wines, as well as on different wine quality parameters, was investigated. Linalool, hotrienol, alpha-terpineol, nerol, geraniol, citronellol, 3,7-dimethylocta-1,5-dien-3,7-diol and the furan and pyran Iinalool oxides were analysed gas chromatographically. Wine quality parameters, such as terpene-like character, cultivar authenticity and overall wine quality of these wines were sensorially evaluated. Increases in grape maturity and the application of juice treatments, like skin-contact and heat treatment, caused significant increases in the concentrations of the majority of terpenes analysed. These changes were, to a limited extent, reflected in the intensities and qualities of some wine characteristics. Heat treatment emerged as the single factor, causing the most prominent increases in terpene concentrations and improvement in overall wine quality.